(untitled) (Research, Society and Development, 2021)
Most antineoplastic agents can cause infusion reactions, the incidence and profile of which vary according to the characteristics of each drug, which may or may not be immune-mediated. In order to describe the profile of immediate adverse reactions to chemotherapy infusion in outpatients, we developed this exploratory, descriptive, cross-sectional and retrospective study, based on records of adverse reaction notifications carried out by the multidisciplinary team from March/2018 to March/2019, and the medical records of the participants. Adverse reactions immediate to chemotherapy infusion were ranked for severity according to the Common Terminology Criteria for Adverse Events and for causality using Naranjo’s algorithm. Of a total of 6,832 intravenous chemotherapy facilities performed during the study period, 30 immediate adverse reactions were recorded, involving 28 patients (83% women), mainly with Paclitaxel (44%) and Carboplatin (20%). According to Naranjo, 60% of infusion reactions were classified as probable. The mean time for onset of reactions was 40 minutes, being the fastest with Docetaxel (5 minutes) and the longest with Paclitaxel (180 minutes). The severity of reactions ranged from mild (64%) to moderate (30%). The most compromised organic segments were respiratory (27%) and cardiovascular (26%); and 83% of the symptoms presented were predicted in the databases. With this study, it was possible to identify the main immediate reactions to the infusion in the study group, as well as the chemotherapeutic agents involved with them, contributing to the safe management of patients and effective control of reactions by the multidisciplinary team.